Angkuh Dalam Perspektif Hadis Tematik - Muhammad Alif; Alan Firgi (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2023)
Arrogance is to think of oneself as superior and superior and to look down on others. Arrogance is caused by several factors, namely: charity and knowledge, lineage, beauty, strength, wealth, lineage, and others. Pride occurs a lot, for example in the family, school, community environment, and anywhere. They act arrogant because they are used to living like that. In the family, for example, parents always accustom their children to always be arrogant. An arrogant person likes praise, he wants to always occupy the top position, doesn't want to be advised, thinks he is the most righteous. Even though such an attitude is not justified in association, especially in Islam. Allah really hates people who act arrogantly, anyone who cannot get rid of that trait, Allah will put him in the most despicable place, namely hell. A person can change, as long as he really wants to change it, namely by believing in the Qur'an, the way to do it is by reading it and understanding the meaning contained in it. Then by memorizing the Qur'an, because by memorizing one's heart will always be close to the Qur'an, do not have time and do not want to do things that can damage faith. And of course the clarity about this arrogance has been explained below in the form of thematic hadith. Adjustment of existing themes so that they can be easily understood to clarify the concept of arrogance from a hadith perspective.